Concurrent timed port automata - Grosu, Radu; Rumpe, Bernhard 1967- (1995)
Abstract: "We present a new and powerful class of automata which are explicitly concurrent and allow a very simple definition of composition. The novelty of these automata is their time-synchronous message-asynchronous communication mechanism. Time synchrony is obtained by using a global clock. Message asynchrony is obtained by requiring the automata to react to every input. Explicit concurrency is obtained by marking each transition with a set of input and output messages. We compare these automata with a history based approach which uses the same communication mechanism and show that they are equivalent."
Keywords: Data flow computing; Data structures (Computer science); Machine theory